Émile Benveniste em suas últimas aulas no Collège de France: a escrita em questão - Rocha, Aline Wieczikovski (2019)
This research proposes a study on writing. Specifically, it seeks to respond, as a matter of thesis, what is the differential in Émile Benveniste thinking about writing. The proposal starts from the theoretical foundations of Émile Benveniste, present in his Last Lectures: Collège de France, 1968 and 1969 and in his two tomes of Problems in General Linguistics. The research establishes as general objective to verify how the linguist elaborates the writing problem on the linguistic dimension in its theoretical frame. To guide the research process, the following specific objectives were drawn: (re) constitute the scientific scenery about writing at the time that precedes Émile Benveniste Last Lectures; comprehend the motivations of Benveniste related to the writing, from the Course in General Linguistics reading; and, with this, situate the Saussurian discussion itself about writing; discuss the lessons about semiology and the relationship on language and writing; finally, to inscribe the significance of writing from the Benvenistian frame. Regarding the research objectives, they are determined as exploratory and descriptive, since they allow a new way of seeing the theme of this thesis, while the discover y of this last reflection of Benveniste is presented. The research fits as qualitative. It is also proposed a corpus to proceed the writing analysis. It is about the newspaper Pato Macho, which circulated in Rio Grande do Sul, especially in Porto Alegre, in 1971, for fifteen weeks. As part of the results, it is observed that, by operating the property of the language double significance, Benveniste finds that writing presents itself as a secondary form of the speaking, therefore, a secondary form of discourse, forge of the two ways of being language: language as semiotic, language as semantic. Writing shows itself, thus, a privileged place for the observation of language.